Hepatocurative potential of Vitex doniana root bark, stem bark and leaves extracts against CCl4–induced liver damage in rats - James Dorcas Bolanle; Kadejo Olubukola Adetoro; Sallau Abdullahi Balarabe; Owolabi Olumuyiwa Adeyemi (Asian Pacific Journal of Tropical Biomedicine, 2014)
Objective: To evaluate the hepatocurative effects of aqueous root bark, stem bark and leaves of Vitex doniana in carbon tetrachloride (CCl4) induced liver damage and non induced liver damage albino rats. Methods: A total of 60 albino rats (36 induced liver damage and 24 non induced liver damage) were assigned into liver damage and non liver damage groups of 6 rats in a group. The animals in the CCl4 induced liver damage groups, were induced by intraperitoneal injection with a single dose of CCl4 (1 mL/kg body weight) as a 1:1(v/v) solution in olive oil and were fasted for 36 h before the subsequent treatment with aqueous root bark, stem bark and leaves extracts of Vitex doniana and vitamin E as standard drug (100 mg/kg body weight per day) for 21 d, while the animals in the non induced groups were only treated with the daily oral administration of these extracts at the same dose. The administration of CCl4 was done once a week for a period of 3 weeks. Results: There was significant (P<0.05) increase in concentration of all liver marker enzymes, alanine aminotransferase, aspartate aminotransferase and alkaline aminotransferase (ALT, AST and ALP) and significant (P<0.05) decrease in albumin in the CCl4 induced liver damage control when compared to the normal control. The extracts caused a significant (P<0.05) reduction in the serum activities of liver marker enzymes (ALT, AST and ALP) and a significant (P<0.05) increase in albumin of all the induced treated groups. Only stem bark extract and vitamin E significantly (P<0.05) increased total protein. All the extracts significantly (P<0.05) lowered serum creatinine whereas only root bark extract significantly (P<0.05) lowered serum level of urea in the rats with CCl4 induced liver damage. Conclusion: Hepatocurative study shows that all the plant parts (root bark, stem bark and leaves) possess significant hepatocurative properties among other therapeutic values justifying their use in folklore medicine.